Messianismo tardio : adorno e a persistência da teologia política - Santos, Jéverton Soares dos (2019)
The subject-matter of this doctoral dissertation is the thought of Theodor Wiesengrund Adorno. Its goal is to examine pari passu the role that a messianic strand of Jewish source has in Adornian philosophy. The exegetical strategy adopted by the thesis is that of a diachroniccomparative nature, since one tries to reconstruct the influences of schools, concepts and authors in the development of the philosophical work of Adorno, with a view to solving some problems of understanding that arise from the reading and discussion of his main works and essays. Broadly speaking, this work consists of a modest attempt to offer an interpretation of Adorno's thought that may extend well beyond the disciplines of aesthetics, psychoanalysis, and social theory, in which the author has a larger circle of readers and scholars. However, one does not intend to reinvent the wheel, disavowing a long and consolidated academic reception of the Frankfurter philosopher. That the theological motives, especially stemming from Jewish traditions, left traces in Adorno's thought is something widely recognized by the reception, not being object of problematization neither here nor elsewhere. But what is still in dispute is whether these theological traces configure structural aspects of his critical theory, or whether they are, on the contrary, only conceptual residues of a casuistic interest. From the point of view adopted by this work, we opted to position in favor of the first option, that is, in favor of the thesis less accepted by the reception. That is why one had to construct a hermeneutic proper to Adorno's thought, from the Jewish figure of messianism, which appears at different times and diffusely throughout his philosophical trajectory, but which reaches, in a later period of his thought, a meaning too great to ignore. In this way, four thematic periodizations were created to explore different moments of Adorno's thinking, namely: 1) the metaphysics of youth (1919-1931), 2) the philosophy of history (1932-1947), 3) late messianism (1935-1969) and 4) the persistence of political theology (1940s). Although they are not arbitrary, they have a didactic rather than compartmentalized character and do not necessarily rival each other. They seek to emphasize rather the discontinuities and ruptures within his philosophical discourse than to reaffirm a supposed cohesion of his philosophy as a whole. Thus, my thesis is that this messianic aspect should not be understood in a purely negative way, that is, based only on the Jewish interdiction of positively representing paradise, social utopia and full justice, but also of positive form, through a model of political theology committed to redemption while demythologizing it. With this model of political theology, Adorno identifies and fights, with rigorous argumentation, the antisemitic – and therefore, mythical - vestiges within the philosophical systems. After Auschwitz, the Jewish people came to be portrayed by the author as the historical paradigm of the non-identical that the philosophy of identity sought to eliminate at all costs. For this reason, the dissertation emphasizes the persistence of political theology, which takes on Adorno the form of a relentless criticism of the philosophies of Hegel and Heidegger, as incarnations of the phenomenon of spiritual antisemitism – which is based on premises of metaphysics (or theodicy) to legitimize ontologically evil, death and suffering in the world. Thus, Adorno's late philosophy demonstrates that criticism of idolatry must first of all be critique of ontology as a worship of being.